GC-MS ANALYSIS AND IDENTIFICATION OF BIOACTIVE CONSTITUENTS FROM FLOWERS OF TODDALIA ASIATICA (RUTACEAE) - NARAYANAN RAVISANKAR; ABUBAKKER SIDDIQ; SOORIAMUTHU SEENI; JERRINE JOSEPH (International Journal of Pharma and Bio Sciences, 2015)
The herbal market is flooded with substitutes and adulterants due to non-availability of the genuine drug and poor knowledge and difficulty in identifying the pure active principle. Toddalia asiatica (Rutaceae) is a constituent of traditional systems of medicine used for treating a paradigm of diseases. The flowers were extracted with methanol, the filtered extract was concentrated to dryness and the residue subjected to GC-MS analysis. The results showed the presence of diverse bioactive compounds such as dihydroxyacetone, propylcarbamate, 4H- pyran-4-one, 2,3 - dihydro-3,5-dihydroxy-6-methyl, 5-hydroxymethylfurfural, Dichloropropylphospine,5-Ethyl-2,4-dimethyl isoxazolidine,oleic acid, 4,5- diamino-2-hydroxypyrimidine, cyclopentanone dimethylhydrazone, 4-mercaptophenol, 2,4-dihydroxy-2,5-dimethyl-3(2H)-furan-3-one, Deferoxamine, 1,2,3-propanetriol,1-acetate, butanenitrile,2,3,-dioxo-dioxime,o,o-diacetyl, acetamide,N-butyl, 3-pentanol,2,3,4-trimethyl, 1,3-dioxolane,2-butyl-2-methyl, n-Hexadecanoic acid, Urea,N,N’-dibutyl- N,N’-dimethyl and Cis-13-Octadecenoic acid with varying chemical structures that are specific to floral tissues, this vouches for phytochemical potential of T.asiatica flowers and is indicative of their medicinal use.